2010
DOI: 10.1063/1.3432623
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous water nucleation and droplet growth in methane and carbon dioxide mixtures at 235 K and 10 bar

Abstract: Homogeneous nucleation rates and droplet growth rates of water in pure methane and mixtures of methane and carbon dioxide were measured in an expansion wave tube at 235 K and 10 bar. The nucleation rate in pure methane is three orders of magnitude higher than literature nucleation rates of water in low-pressure helium or argon. Addition of carbon dioxide to the carrier gas mixture increases the rates even more. Specifically, rates in a mixture of methane and 3% carbon dioxide are a factor of 10 higher than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…In brief, the gaps for the kinetic model for heterogeneous condensation on an insoluble spherical particle have been overcome by taking two mechanisms of cluster growth and the effect of line tension into account (Eqs. (8), (27), and (23)), and deriving the exact expression for evaporation coefficient (Eqs. (27)-(29)).…”
Section: Kinetic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, the gaps for the kinetic model for heterogeneous condensation on an insoluble spherical particle have been overcome by taking two mechanisms of cluster growth and the effect of line tension into account (Eqs. (8), (27), and (23)), and deriving the exact expression for evaporation coefficient (Eqs. (27)-(29)).…”
Section: Kinetic Modelmentioning
confidence: 99%
“…6 As a result, the growth rate of single droplet with a large Knudsen number can approximately be given by the difference of the condensation coefficient and the evaporation coefficient. 8 For heterogeneous condensation on an insoluble spherical particle, the growth rate of a droplet is dr…”
Section: Growth Rate Of Droplet In Heterogeneous Condensationmentioning
confidence: 99%
“…The Pulse Expansion Chamber experimental setup is explained by [1] and [2]. The setup simplified Process Flow Diagram is shown in Gas mixture could be brought into a thermodynamic state of non-equilibrium by subjecting it to a sudden change in temperature and pressure.…”
Section: Description Of Test Setupmentioning
confidence: 99%
“…The above nucleation and crystallization theories could be empirically proven by two experimental methods namely Pulse Expansion Wave Tube (PEWT) and Pulse Expansion Cell (PEC) [1,2,3]. In this exercise, the PEC was chosen to perform the test mainly due to a much shorter (about 8-10 times shorter) turnaround time in between each test, that will enable more tests to be run per test day to get as much variation as possible in term of binary gas mixtures concentrations and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples can be found in literature on the analysis of the cluster composition by exploiting the nucleation theorem (Kashchiev 1982;Oxtoby and Laaksonen 1995;Luijten et al 1998Wölk and Strey 2001;Kalikmanov et al 2007;Holten and van Dongen 2010). At high pressure (>0.2 MPa), only few studies can be found in literature on the analysis of the critical cluster composition for water-carrier gas mixtures Holten and van Dongen 2010). analyzed water-helium, water-nitrogen and n-nonane-methane mixtures at 240 K and 1 MPa, 2.5 MPa and 4 MPa.…”
Section: Introductionmentioning
confidence: 99%